Modified Lengthening Temporalis Myoplasty Involving an Extended Lazy-S Incision to Avoid Facial Scar Formation. Issue 3 (May 2018) - Oji, Tomito; Hayashi, Akiteru; Ogino, Akihiro; Onishi, Kiyoshi
Abstract : Background: Lengthening temporalis myoplasty is a faster and less invasive alternative to free muscle transfer for smile reconstruction. However, it requires a nasolabial fold incision, which leaves a midfacial scar. Based on esthetic considerations, a modified approach, involving an extended lazy-S (parotidectomy) incision instead of a nasolabial fold incision, was developed. Methods: A cadaveric study involving 10 hemifaces was conducted. From February 2013 to March 2016, the modified lengthening temporalis myoplasty procedure was employed in 10 patients. The results were graded from 1 (poor) to 5 (excellent) according to the Terzis grading system. The excursion of the oral commissure was also measured. Results: The extended lazy-S incision provides easy and safe access to the coronoid process and good visibility. The patients' mean age was 56.5 years, and the mean duration of the postoperative follow-up period was 22.2 months. The patients' underlying conditions included acoustic neuroma (n = 2), Bell palsy (n = 3), congenital conditions (n = 2), brain infarction (n = 1), Ramsay Hunt syndrome (n = 1), and malignant parotid lymphoma (n = 1). One patient suffered a surgical site infection, which was successfully treated with irrigation. All the patients achieved improvements in smile symmetry: 2, 5, and 3 patients obtained excellent, good, and moderate results, respectively. The excursion of the oral commissure ranged from 5 to 10 mm. Conclusion: The modified lengthening temporalis myoplasty procedure provides satisfactory functional outcomes without causing significant complications. It does not leave a facial scar and is a preferable option, especially for young and female patients, and patients who have undergone ablative surgery involving the parotid region. Abstract : Supplemental Digital Content is available in the text